(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Commercially available soft drinks i.e., Sprite and 7up (lemon) samples of 10 different batches were studied by UV-Vis spectrophotometry to find out the presence of preservative and stimulant. The wavelength of absorption maxima (?max) was 224 nm for sodium benzoate and 272 nm for caffeine. The soft drink samples were degassed, extracted with HPLC grade water and cleaned up to study sodium benzoate and caffeine content. The average quantity of caffeine was in the range of 22 to 30 ?g/ml in Sprite and 20 to 30 ?g/ml in 7up (lemon), whereas the average quantity of sodium benzoate was in the range of 181 to 191 ?g/ml in Sprite and 140 to 160 ?g/ml in 7up (lemon) samples. The correlation coefficients of the calibration curves of sodium benzoate and caffeine were found to be 0.9972 and 0.9862, respectively. Recovery experiment was done by spiking sodium benzoate at 20 ?g/ml level with 10 replicate studies. The mean recovery of sodium benzoate was 89.14 ± 2.14 %. The reproducibility and repeatability of the method was very satisfactory with low value of RSD. The present method can be successfully applied for the study of sodium benzoate and caffeine in commercial soft drinks. Bangladesh Pharmaceutical Journal 19(1): 68-74, 2016